A Trend Analysis of Business Funding Patterns and Sources Among Student Entrepreneurs at the Institute of Higher Learning Level : Implications for Entrepreneurship Education and Support Programs - Ikhsan, Nurzaki; MOHD ALIAS, MOHD AZUAN; NIK ROSELEY, NIK ROSELINA; HASAN, ZAKIYAH (Lembaga Penelitian Publikasi dan Pengabdian Masyarakat LSPR, 2023)
Business funding plays a pivotal role in facilitating entrepreneurial ventures, enabling them to initiate or expand their businesses effectively. Diverse funding sources, such as personal savings, venture capital, business angels, business loans, and government assistance, have been recognized as crucial means of financial support. However, for student entrepreneurs currently pursuing higher education, the suitability of these funding options is subject to several complexities. The inexperience in commencing a business, the commitment to academic pursuits, and adherence to specific student policies and eligibility criteria necessitate a more tailored analysis. Therefore, this paper delves into a trend analysis of business funding exclusively among student entrepreneurs. Drawing on data sourced from the esteemed Malaysian Academy of SME & Entrepreneurship Development (MASMED), at Universiti Teknologi MARA (UiTM), Malaysia, this study investigates business funding sources, business funds secured, business categories, and the level of student involvement over multiple years. This empirical examination and subsequent discussion provide invaluable insights into discerning patterns and shifts in student entrepreneurial business funding strategies. By scrutinizing these trends, a prediction students' decisions to venture into entrepreneurship, particularly with regards to securing adequate business funding can be developed. Furthermore, this study's findings pave the way for more comprehensive investigations, guiding potential policy enforcements in both governmental and private sectors pertaining to business funding. Ultimately, the elucidation of these trends contributes to fostering an ecosystem conducive to the growth and sustenance of student-led enterprises, unlocking new avenues for economic and societal development.